Mycotoxins in Feedstuffs - Weidenbörner, Martin. (Springer New York : Imprint: Springer, 2007)
Feedstuff is any of the constituent nutrients of an animal ration. The plants used in feed, such as grains, oils seeds, and nuts root crops, are susceptible to mycotoxin contamination. Mycotoxins in Feedstuffs provides an overview of mycotoxins in feedstuff and ingredients. It discusses whether a feedstuff ingredient is predisposed for a mycotoxin contamination and lists the degree of contamination, the concentration of the toxins and the country of origin and/or detection of the contaminated food. About the Author: Dr. Martin Weidenbörner is a professor emeritus of the Institute for Applied Microbiology of Germany.